Unpacking Global Shocks - Alejandro G. Graziano; Yuan Tian (CESifo GmbH, 2024)
Economy-wide shocks affect demand, supply, and intermediary sectors simultaneously. We dissect the impact of the Covid-19 pandemic on international trade by combining information from customs records, smartphone-based human mobility, and container ship port calls. We find that local disruptions to domestic demand reduced import quantities, while local disruptions to foreign supply and at seaports increased import prices and reduced quantities. On net, local disruptions during the pandemic were a negative supply shock, and the residual structural factors were a positive demand shock. The resulting excess import demand contributed to the rise in domestic inflation.
Keywords: F10; F14; F16; I12; I18; R41; 330; international trade; local disruptions; human mobility; shipping costs; Covid-19 pandemic; inflation